ANALISIS PERBANDINGAN POTENSI PENERIMAAN DAN EFEKTIFITAS PAJAK PENERANGAN JALAN KABUPATEN MINAHASA SELATAN DAN KABUPATEN MINAHASA TENGGARA - Ibrahim, Driyana; Sondakh, Jullie J; Wangkar, Anneke (Universitas Sam Ratulangi, 2016)
In an effort to improve the implementation of development and service to the community as well as increased economic growth in the region, the one source of regional revenue from tax sector in particular, is the street lighting tax. In accordance with Law No. 28 of 2009 Article 1 number 28, street lighting tax (RPM) is a tax on the use of electricity, either generated themselves or obtained from other sources. The purpose of this study was to determine the level comparison of the revenue potential and effectiveness of street lighting tax in South Minahasa District and Southeast Minahasa Regency 2011-2015. This research was conducted in South Minahasa District DPPKAD and DISPENDA Southeast Minahasa Regency. The analytical method used was descriptive qualitative method. Based on the results of this study concluded that there are differences in the potential of street lighting tax receipts between the South Minahasa District and Southeast Minahasa Regency in the years 2011-2015, but there was no difference in the effectiveness of street lighting tax receipts between the South Minahasa District and Southeast Minahasa Regency 2011-2015. Street lighting tax revenue as one of the biggest areas in the South Minahasa District and Southeast Minahasa Regency is expected to be a mobilizer of local taxes in the regencies of them. Keywords: street lighting tax, potential, effectiveness.